Efficiency and non-performing loans of comparison between commercial banks in Indonesia and Malaysia - Setiawan, Chandra; Lumban Tobing, Joseph Utama (Junal Ilmu Manajemen, 2024)
Banks play a pivotal role in the economy, serving as intermediaries between those with excess funds and those needing funds. They contribute to both micro and macroeconomic activities in a country. Malaysian banks are operating in Indonesia, some of which have become the largest banks in the country. However, Indonesian banks face challenges in expanding their business in Malaysia. This research investigates the efficiency and determinants of non-performing loans (NPL) of commercial banks in Indonesia and Malaysia from 2014 to 2018. The study utilized variables such as Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Gross Domestic Product (GDP), Inflation (INFL), and Return on Asset (ROA) of NPL as determinants. The Data Envelopment Analysis (DEA) approach was used to measure the technical efficiency of commercial banks in both countries, and panel regression was used to find the determinants of efficiency and NPL. The findings show that most banks in Indonesia have relatively low efficiency, while banks in Malaysia have high efficiency. However, there was no significant difference between the efficiency of commercial banks in Indonesia and Malaysia. The study also revealed that ROA significantly affected NPL and efficiency for commercial banks in both countries. In contrast, CAR and GDP did not significantly affect NPL and efficiency